EXTENSION OF RIGHTS FOR BUILDING BY THE LIMITED LIABILITY REVIEWED FROM LEGAL CERTAINTY, JUSTICE AND TOWARDS SUSTAINABLE INVESTMENTS AND PEOPLE’S WELFARE - I Nyoman Alit Puspadma (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTUUPA HGB regulates the extension of Article 35 paragraph (2), which containsfuzziness norm. The word